Belief of Customers in Social Commerce Performed via Social Networking Sites: An Empirical Study from Hồ Chí Minh City - Công Thảo Tiên Phan; Quan Trí ặng; Thành Luân Nguyễn (Vietnam Social Sciences, 2023)
While e-commerce emphasizes platform-based trust and security, social media platforms are not liable for users' posts and comments during social commerce (s-commerce) activities. Additionally, the impact of customer trust on their attitudes and willingness to engage in s-commerce remains largely unexplored. This study aims to develop a theoretical model that examines the influence of trustee characteristics on customer trust, attitude, and willingness to buy, using the theory of reasoned action (TRA). A survey was conducted, collecting 200 valid questionnaires from customers in Vietnam who use Instagram, Facebook, Twitter, and TikTok. Firstly, the study confirms that perceived reputation, multichannel integration (MTI), and system assurance positively influence customer trust, which subsequently affects customer attitude and leads to a willingness to purchase. Secondly, a neural network model was employed to rank the relatively significant predictors obtained from structural equation modeling (SEM). This study contributes to the growing literature on the use of social networking site (SNS) apps in boosting e-commerce businesses. The novel methodology and findings from this study significantly contribute to the existing literature on e-commerce settings. Therefore, for practitioners aiming to build trust in their SNS-based businesses, the findings highlight the importance of trust in s-commerce and recommend an integrated approach based on the key findings of this study.
Keywords: 330